PENGATURAN KOALISI PARTAI POLITIK DALAM PENENTUAN PASANGAN CALON PRESIDEN PADA SISTEM KETATANEGARAAN INDONESIA - Rahmat Bijak Setiawan Sapii (2022)
The coalition of political parties presence in president pair candidacy for election has been required by the 1945 Constitution of the Republic of Indonesia. Furthermore, the 1945 Constitution of Republic Indonesia Article 8 paragraph (3) has implicitly wished for a stable and long-term coalition of political parties. However in fact, these coalition tends to be pragmatic, unstable and short-term. This is indicated by the composition disparity of pre-election coalition and government coalition This paper aims to complement the lack of previous studies by thoroughly examining political party coalitions on regulating president candidates pair in Indonesian constitutional system and the implications for effective governance. The research method used is normative legal research using primary legal materials, secondary legal materials and tertiary legal materials. The study affirmed that there is a necessity to explicitly regulate coalition reregistration for pre-election that will take on second round as well as an agreement for transforming pre-election coalitions to become government coalitions at the level of legislation. This is done with presidential threshold reconstruction.